2022
DOI: 10.1002/sres.2874
|View full text |Cite
|
Sign up to set email alerts
|

From ideas to entrepreneurial opportunity: A study on AI

Abstract: Artificial intelligence technology is applied in numerous fields. Several countries around the world have introduced national policies on artificial intelligence, and the competition for this emerging technology has become an important driving force for industrial development. In recent years, interdisciplinary research on artificial intelligence has made great progress. From the perspective of idea‐driven technology entrepreneurship, we discuss the concept of AI with other emerging technologies. For the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The earlier assumes that opportunities are objective events that come from exogenous shocks, like technological changes, and they need to be explored. The latter supposes the opportunities are not available and are subjectively created through a continuous search of action and re-action by the entrepreneurs, which could be accelerated by technological enhancement (Ge et al, 2022). By emphasizing that both views are not independent, Mary George et al (2016) found six factors affecting opportunity recognition by entrepreneurs, including prior knowledge, social capital, cognition, environmental conditions, entrepreneurial alertness, and systematic search.…”
Section: Literature Review 21 Entrepreneurial Opportunity Recognition...mentioning
confidence: 99%
“…The earlier assumes that opportunities are objective events that come from exogenous shocks, like technological changes, and they need to be explored. The latter supposes the opportunities are not available and are subjectively created through a continuous search of action and re-action by the entrepreneurs, which could be accelerated by technological enhancement (Ge et al, 2022). By emphasizing that both views are not independent, Mary George et al (2016) found six factors affecting opportunity recognition by entrepreneurs, including prior knowledge, social capital, cognition, environmental conditions, entrepreneurial alertness, and systematic search.…”
Section: Literature Review 21 Entrepreneurial Opportunity Recognition...mentioning
confidence: 99%
“…AI may impact venture processes and practices. Research has been conducted on how AI can enhance entrepreneurial activities; meanwhile, attention has been shifted towards the entrepreneurial implications of AI (Ge & Zhao, 2022; Ge et al, 2022; Jia et al, 2022; Li, Xie, et al, 2022; Li, Zhang, et al, 2022; Nayyar, 2022; Su et al, 2022; Sun, He, et al, 2022; Sun, Xu, et al, 2022; Wang, 2022; Wang et al, 2022; Yao, Jin, et al, 2022; Yao, Ye, et al, 2022; Zhang et al, 2022; Zhang & Zhang, 2022).…”
mentioning
confidence: 99%